Multiplier Model for Forecasting Manpower Demand - Sing, Michael; Love, Peter; Tam, C. (University of Johannesburg, 2012)
To better manage and forecast the demand for labor in the construction industry, a mathematical model is developed using a distributed lag model and labor multiplier approach. The model is tested using economic statistics and manpower data derived from Hong Kong construction projects. The model can be used by public and private sectors to forecast future labor demand so that an optimal workforce can be attained.